Exploring the utility of Analytic Hierarchy Process (AHP) in ranking livelihood activities for effective and sustainable rural development interventions in developing countries - Baffoe, Gideon (Evaluation and program planning, 2019)
•The study explores the application of the Analytic Hierarchy Process (AHP) in prioritizing livelihood activities.•The AHP approach offered effective and objective way to prioritize competing needs and interests.•The approach has the potential to address the issues of counterproductive and nonstarter project outcomes. It is commonly known that most development projects, especially in the global south, tend to achieve unintended results or fail because of lack of due diligence. Project satisfaction and sustainability would only be achieved if consistent with the actual needs of the people intended to benefit. Based on field experiences in the Fantekwa District of Eastern Ghana, this study aims to explore the utility of the Analytic Hierarchy Process (AHP) in prioritizing livelihood activities to aid in effective and sustainable poverty reduction interventions in developing countries. Data from twenty five development stakeholders in the district were used for the assessment. The study demonstrates that with appropriate data, and systematically following all required processes, the AHP approach can effectively show where intervention is most needed. Application of AHP in the current context, the study argues, has the potential to address the issue of wrong development targeting with associated counterproductive and nonstarter outcomes.